Index to social sciences & humanities proceedings.
Quarterly, with annual cumulation. Listing of published proceedings (consisting of papers presented) of conferences, seminars, symposia, colloquia, conventions, and workshops. Proceedings published in any format are included; those consisting only of abstracts are excluded. Besides the main section of contents of the published proceeding titles, there are indexes by category, author/editor, sponsor, location, subject, and corporate body.